Upaya Masyarakat Muslim Menjaga Identitas Sejarah melalui Pemeliharaan Bangunan Bersejarah di Sei Glugur, Kabupaten Deli Serdang - Darma, Surya; Monang, Sori; Muchsin, Kasron (Medan Resource Center, 2024)
This research investigates the role of Islamic communities in preserving historical buildings in Sei Glugur Village, Pancur Batu Sub-district, Deli Serdang Regency. The study addresses how the Muslim community maintains its cultural identity through these preservation efforts. Using a descriptive qualitative approach, data were collected via observations, interviews with key informants, including the Village Head and building caretakers, as well as documentation. Guided by Indonesian Law No. 11 of 2010 on Cultural Heritage, the research reveals the community’s active role in utilizing and maintaining historical buildings. For example, the Sri Maha Laksmi Temple is still functional, a logistics warehouse was repurposed as a public school, and a Dutch-era house became the Al-Istiqomah Mosque. Factors such as the community’s long-term residence and hereditary ties to colonial-era workers contribute to their preservation awareness. However, some buildings, including the administration office and tobacco warehouse, remain underutilized. The study concludes that community-government partnerships are essential to optimize the use and preservation of these structures. Recommendations include allocating resources for adaptive reuse and emphasizing cultural tourism and local identity enhancement.